The experiential blink: Mapping the cost of working memory encoding onto conscious perception in the attentional blink. (August 2016) - Pincham, Hannah L.; Bowman, H.; Szucs, D.
Abstract: The attentional blink (AB) represents a cognitive deficit in reporting the second of two targets (T2), when that second target appears 200–600 msec after the first (T1). However, it is unclear how this paradigm impacts the subjective visibility (that is, the conscious perception) of T2, and whether the temporal profile of T2 report accuracy matches the temporal profile of subjective visibility. In order to compare report accuracy and subjective visibility, we asked participants to identify T1 and T2, and to rate the subjective visibility of T2 across two experiments. Event-related potentials were also measured. The results revealed different profiles for the report of T2 versus the subjective visibility of T2, particularly when T1 and T2 appeared within 200 msec of one another. Specifically, T2 report accuracy was high but T2 visibility was low when the two targets appeared in close temporal succession, suggesting what we call the Experiential Blink is different from the classic AB. Electrophysiologically, at lag-1, the P3 component was modulated more by subjective visibility than by report accuracy. Collectively, the data indicate that the deficit in accurately reporting T2 is not the same as the deficit in subjectively experiencing T2. This suggests that traditional understandings of the AB may require adjustment and that, consistent with other findings, working memory (WM) encoding and conscious perception may not be synonymous.